Design and Construction of an Automatic Clothes Drying System with Remote Control Using Arduino and WIFI - Ihza Fauzan; Suzuki Syofian (Prodi Teknologi Informasi Universitas Darma Persada, 2026)
This research aims to address the problem of clothes drying, which is often hampered by unpredictable weather conditions in Indonesia, a tropical country with two main seasons: dry and rainy. To solve this problem, we developed an automatic clothes drying system that can be controlled remotely using Arduino and Wi-Fi technology. This system is equipped with temperature sensors, light sensors, and rain sensors that function to detect weather conditions in real-time. This automatic clothes drying system works by closing the clothes drying system when rain is detected and reopening it when the weather is clear. Users can also control the clothes drying system manually through an Android application connected to Wi-Fi. The results of the study indicate that this system functions well according to the planned design. Field testing demonstrated a fast and accurate response from the sensors to weather changes, as well as the ease of use of the Android application for manual control. The conclusion of this study is that this automatic clothes drying system is able to provide a practical and efficient solution for drying clothes, especially in the face of unpredictable weather. This system not only saves time and energy, but also provides extra protection for the clothes being dried.